Performance analysis of spatial multiplexing MIMO-OFDM system with different equalisers and guard intervals. (2016) - Chiali, Imane; Debbat, Fatima; Bendimerad, Fethi Tarik
Multiple-input multiple-output (MIMO) system is a very popular solution in the field of wireless communications, in order to improve the capacity and reliability of radio link. Nevertheless, during any transmission over fading channel, the performance of MIMO system is degraded due to the inter symbol interference (ISI). The combination of orthogonal frequency division multiplexing (MIMO-OFDM) and the use of equalisation at the reception have become very effective to eliminate the (ISI) and reduce the imperfection of the channel. The optimal maximum likelihood (ML) equaliser suffers from high computational complexity. In this context, we propose the combination of vertical bell labs space time (VBLAST) multiplexing and ordered successive interference cancellation (OSIC) equaliser in MIMO-OFDM system, whose performance is compared with different equalisers, in particular zero forcing (ZF), minimum mean square error (MMSE), and ML using cyclic prefix (CP) and zero padding (ZP) intervals in Rayleigh time-selective fading channel. The simulation results show that the performance of ZF/MMSE-OSIC equaliser with ZP-ODFM is close to the ML with a low complexity and it works better as compared to other algorithms.